...but who shall organize the local economy? - Kaufman, Ilona (Acta Scientiarum Socialium, 2013)
...but who shall organize the local economy? When looking for tools for recovering from the present economic crisis, the streghtening of local economies often arises as a possible alternative. The aim of the present paper is to examine which organization can best be capable of organizing and coordinating a local economy. We shall look for an organization that has a live connection to the rural business sector. Our micro-regional research in 2011came to the conclusion that local governments are the best candidates for this role and that social economy might be the best form for fulfilling this function.